Pore modification mechanisms in a deeply buried non-marine sandstone: the Early Cretaceous Upper Sarir Sandstone Formation, Sirte Basin, Libya. - Adepehin, Ekundayo Joseph (Elsevier, 2021)
Critical understanding of the reservoir pore-system is crucial for effective fluid-flow. Core-sedimentological description (40 core plugs), petrography (thin section and scanning electron microscopy with energy dispersive spectrometry), x-ray diffractometry, and high-resolution imaging were integrated to characterize pore-modification processes in a deeply buried (ca. 12470–12558 Ft.) non-marine sandstone. The reservoir is dominantly subrounded to subangular, well-sorted to moderately well-sorted, and medium-to fine-grained quartz arenite and lithearenite. Framework ranges from matrix-supported to matrix-devoided types. With a mean point-counted composition of Q95F0L5, quartz is the dominant mineral in all samples. Core-derived porosity and permeability range from 0.88 to 16.89% (Average 9.99%) and ~0.00–431.06 mD (Average 66.42 mD), respectively. Intergranular (ɸI), micro (ɸμ), fracture (CF), and dissolution (Diss) porosities constitute an estimated 60%, 35%, 3%, and 2% of the total porosity. The pore-spaces are randomly distributed and largely disconnected from one another. Connected pores are linked by necking, tubular, and lamellar pore throats. Pore-destructive diagenetic processes occurred mainly in the early-intermediate diagenetic phase, and to lesser extent in the late diagenetic phase. Pore-enhancement processes were of sparse occurrences. Mechanical compaction, quartz overgrowth development, kaolinitization, sideritization, and calcite cementation are the main pore-occluding processes identified. Quartz overgrowth increased with depth and it shows an inverse relationship with poro-perm. The formation of quartz overgrowth haloes in the Upper Sarir Sandstone Formation were most likely formed from non-insitu silica mobilized into the pore system during post-rift cooling. This study confirms the need for careful heterogeneity modelling even in non-marine deposited reservoir sandstone, notwithstanding their known clean nature in contrast to mud-rich marine reservoirs.